PENERAPAN TUT WURI HANDAYANI PADA PESERTA KURSUS DAN PELATIHAN (LKP) AR-RUM YOGYAKARTA - Anggi Kusuma Wardani (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2020)
The purpose of this study was to determine the application of the Tut Wuri HandayaniÂ  method in Lembaga Kursus dan Pelatihan (LKP) AR-RUM Yogyakarta especially in sewing courses class. The method has a definition, function, and purpose to develop students creativity. The kind of this research is a descriptive qualitative reserch. The source of this research is from the leader and instructor of LKP AR-RUM. Data collection techniques carried out by interview, observation, and documentation. Checking the validity of the data using triangulation of sources, techniques, and time. The data analysis technique used is the Milles and Huberman model in which the researcher carries out data collection, reduction, data presentation, and conclusion drawing. This is the result of the research the implementation of the Tut Wuri Handayani method to develop creativity is focused on the among system by maintaining, fostering, and educating students with compassion, family spirit based on nature and independence.Â